The role of positron emission tomography/CT in hypoxic ischaemic encephalopathy in children - Koc, Zehra Pinar (BMJ Publishing Group, 2013)
The role of positron emission tomography/CT (PET/CT) in diagnosis and follow-up of newborns with hypoxic ischaemic encephalopathy has been documented before; however, this is the first presentation of elder children with both diagnostic and follow-up PET/CT results as far as we know.